Single‐extracellular vesicle (EV) analyses validate the use of L1 Cell Adhesion Molecule (L1CAM) as a reliable biomarker of neuron‐derived EVs - Nogueras‐Ortiz, Carlos J; Eren, Erden; Yao, Pamela; Calzada, Elizabeth; Dunn, Christopher; Volpert, Olga; Delgado‐Peraza, Francheska; Mustapic, Maja; Lyashkov, Alexey; Rubio, F Javier; Vreones, Michael; Cheng, Lesley; et al. (Journal of extracellular vesicles, 2024)
Isolation of neuron‐derived extracellular vesicles (NDEVs) with L1 Cell Adhesion Molecule (L1CAM)‐specific antibodies has been widely used to identify blood biomarkers of CNS disorders. However, full methodological validation requires demonstration of L1CAM in individual NDEVs and lower levels or absence of L1CAM in individual EVs from other cells. Here, we used multiple single‐EV techniques to establish the neuronal origin and determine the abundance of L1CAM‐positive EVs in human blood. L1CAM epitopes of the ectodomain are shown to be co‐expressed on single‐EVs with the neuronal proteins β‐III‐tubulin, GAP43, and VAMP2, the levels of which increase in parallel with the enrichment of L1CAM‐positive EVs. Levels of L1CAM‐positive EVs carrying the neuronal proteins VAMP2 and β‐III‐tubulin range from 30% to 63%, in contrast to 0.8%–3.9% of L1CAM‐negative EVs. Plasma fluid‐phase L1CAM does not bind to single‐EVs. Our findings support the use of L1CAM as a target for isolating plasma NDEVs and leveraging their cargo to identify biomarkers reflecting neuronal function. Previous research suggest that extracellular vesicles (EVs) secreted by brain neurons carry L1CAM and circulate in peripheral blood, coexisting with L1CAM‐positive EVs from peripheral cellular sources and free L1CAM peptides (top left). These other versions of L1CAM in blood challenge the approach of targeting L1CAM for the immunoaffinity isolation of neuronal EVs (top right), a methodology widely adopted to derive blood biomarkers for brain disorders. To further understand L1CAM‐positive EVs, we sought to establish their neuronal origin and determine the abundance of L1CAM‐positive neuronal EVs in human blood using single‐, intact‐EV techniques including flow cytometry, confocal microscopy and a novel Simoa® assay specific for L1CAM in EVs carrying tetraspanins CD9, CD63 and CD81 (bottom left). Results demonstrate that L1CAM ectodomain epitopes are co‐expressed on blood‐derived EVs with the neuronal proteins β‐III‐tubulin, GAP43, and VAMP2, the levels of which increase in parallel with the enrichment of L1CAM‐positive EVs via L1CAM immunocapture (bottom right). Results further validate the use of L1CAM as a target for the immunoaffinity isolation of neuron‐derived EVs from blood.